Interventions to improve tolerability of local anesthetic intradetrusor Botulinum toxin injections: A systematic review. Issue 1 (23rd October 2022) - Faure Walker, Nicholas; Macpherson, Finn; Tasleem, Ali; Rampal, Tarannum
Abstract: Introduction: Intradetrusor BotulinumtoxinA (BTA) injections are recommended for patients with overactive bladder (OAB) refractory to lifestyle changes and medical intervention. It is preferable to perform injections using a flexible cystoscope under local anesthetic (LA) rather than under spinal or general anesthetic owing to the associated anesthetic risks, increased costs, and need for repeated inpatient admission. Injections under LA can be difficult to tolerate for some patients. This review aims to assess interventions that may improve the tolerability of intradetrusor BTA injections under LA. Methods: A systematic review was performed using Ovid of Embase + Embase classic and MEDLINE® ALL in November 2021. Articles were included if they reported objectively measured pain scores during LA intradetrusor BTA injections for refractory OAB. The risk of bias was assessed using Cochrane risk of bias tools. Meta‐analysis was not performed owing to the heterogeneity of outcome measures. Results: Ten studies were included in this review with a total of 429 participants. The review identified alkalinized lidocaine, electromotive drug administration (EMDA), opiate suppositories, lidocaine bladder instillations, number of injections, and dose of BTA as interventions aimed at improving tolerability. Conclusion: EMDA of intravesical alkalinized lidocaine, intravesical, alkalinized lidocaine without EMDA, and a reduction in the number of injection site were all associated with improvements in patient tolerability during LA BTA injections. Further research should address which subgroups of patients find the procedure most painful and would benefit most from these interventions.